(untitled) (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Allergic pathology remains a global problem of humanity. Despite a wide range of anti-allergic drugs, the problem of developing reasonable and safe measures for allergic diseases (ADs) treatment and prevention remains unresolved. Among existing modern therapeutic measures, particular attention is drawn to the allergen-specific immunotherapy. It seems promising to use the cryopreserved pigskin substrate (CPSS), cellular elements of which serve as the source of antigens and are capable of triggering immunotolerance mechanisms. We investigated the effect of CPSS on the development of mouse immunodeficiency and an allergic reaction of delayed-type hypersensitivity (DTH). Materials and Methods: The effect of CPSS on the development of mouse immunodeficiency induced by hydrocortisone acetate (once, intraperitoneally, 250 mg/kg,) was investigated. The CPSS was administered on a daily basis into the stomach of animals as a suspension emulsified with Tween at dosas 200 mg/kg and 500 mg/kg. As the reference drug, we used an analog regarding pharmacological action, the immunostimulatory agent of natural origin thymalin, lyophilisate for solution for injections (100 mg/kg, intraperitoneally). Blood serum of experimental animals was analyzed to assess parameters of the humoral component of the immune system, namely, titers of hemolysins and hemagglutinins and the number of antibody-forming cells according to Ierne and Nordin. The effect of CPSS on development an allergic reaction of DTH induced by skin sensitization with a 5% 2,4-dinitrochlorobenzene (DNCB) solution (five applications of three drops of a 5% alcohol-acetone solution (1:1) of 2,4-DNCB to the animal skin. Four days after the last application, three drops of the 5% 2,4-DNCB solution were applied to the right paw of an animal (initiation of the allergic reaction) was investigated. As the reference drug, we used loratadine tablets, at a dose of 1 mg/kg. Popliteal lymph nodes were removed and weighed. DTH reaction index was determined. The concentration of IgE, as well as the level of tumor necrosis factor-Î± (TFN-Î±), interleukin-2 (IL-2), and IL-10 cytokines, were assessed in blood serum of sensitized animals. Neutrophil phagocytic activity was determined in whole-blood after coincubation of neutrophils with yeast cells. Results: The study established that preventive administration of the CPSS contributes to restoring the balance between cellular and humoral immune responses, which results in inhibition of the pathological process, reduction in specific hyperresponsiveness of tissues to proinflammatory mediators, and reduction of signs of allergic inflammation or immunodeficiency states. Conclusions: Ð reventive administration of the CPSS contributes to restoring the balance between cellular and humoral immune responses, which results in inhibition of the pathological process, reduction in specific hyperresponsiveness of tissues to pro-inflammatory mediators, and reduction of signs of allergic inflammation or immunodeficiency states.